FA06Ma.9Sec1Sol3

FA06Ma.9Sec1Sol3 - f ( x ) = x ( x 2-1) and g ( x ) = x on...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
SOLUTIONS TO HOMEWORK 3 MATH 1A (SECTION 1) FALL 2006 MANWAH LILIAN WONG* Question 1(a) - Apostol 1.26.10 (pg 83) Z 3 2 (3 x 2 - 4 x + 2) dx = (3 x 3 3 - 4 x 2 2 + 2 x ) | 3 2 = ( x 3 - 2 x 2 + 2 x ) | 3 2 = (3 3 - 2(3 2 ) + 2(3) - 2 3 - 2(2 2 ) + 2(2) = 11 Question 1(b) - Apostol 1.26.15 (pg 83) Z 2 0 ( x - 1)(3 x - 1) dx = Z 2 0 3 x 2 - 4 x + 1 dx = 3 x 3 3 - 4 x 2 2 + xdx | 2 0 = 2 Question 2 - Apostol 1.26.21 (pg 83) ( a ) Z c 0 x (1 - x ) dx = Z c 0 ( x - x 2 ) dx = ( x 2 - x 3 3 ) | c 0 = c 2 - c 3 3 Hence, c = 0 , 3 2 . (b) The clumsy way: note that x (1 - x ) 0 when 0 x 1 and x (1 - x ) 0 when x 0 or x 1. Suppose c 1. Then the argument is the same as in part (a), and c = 0 , 3 2 . If c > 1, then the Date : October 11th, 2006. * MC 253-37, Mathematics Department, California Institute of Technology, Pasadena, CA 91125, USA. E-mail: wongmw@caltech.edu. 1
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
2 M.-W. L. WONG problem becomes solving for R 1 0 x (1 - x ) dx + R c 1 - x (1 - x ) dx = 0, which is equivalent to solving R 1 0 x (1 - x ) dx = R c 1 x (1 - x ) dx = 0. This implies 1 / 3 = c 2 / 2 - c 3 / 3 and by plotting it we know that this happens when c < 0. Contradiction. The clever way: Note that | x (1 - x ) | > 0 x 6 = 0 , 1, hence unless c = 0, Z c 0 | x (1 - x ) | dx > 0 . Question 3 - Apostol 2.4.10 (pg 94) Consider
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: f ( x ) = x ( x 2-1) and g ( x ) = x on the interval [-1 , 2]. Note that g f on [0 , 2] and f g on [-1 , 0]. Hence the area of S is: Area ( S ) = Z-1 x ( x 2-1)-xdx + Z 2 x-x ( x 2-1) dx = Z-1 x 3-2 xdx + Z 2 2 x-x 3 dx = 7 / 4 Question 4 - Apostol 2.4.16 (pg 94) Consider f ( x ) = x-x 2 and g ( x ) = ax . We need to decide on the conditions on a such that f ( x ) g ( x ). If a 1, then we must have 1-a x 0. If a 1, then 0 x (1-a ). If a 1, then the area is R 1-a x (1-a )-x 2 dx =-(1-a ) 3 / 6. Hence a = 4. If a 1, then the area is R 1-a x-x ( x 2-1) dx , implying a =-2 Question 5 - Apostol 2.5.18 (pg 105) Z ( x + sin x ) dx = x 2 2-cos x | = 2 2 + 2...
View Full Document

Page1 / 2

FA06Ma.9Sec1Sol3 - f ( x ) = x ( x 2-1) and g ( x ) = x on...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online